The effects of entrepreneurial orientation dimensions on performance in the tourism sector - Nicoletta Fadda (New England Journal of Entrepreneurship (NEJE), 2018)
Purpose - The purpose of this paper is to examine the influence of entrepreneurial orientation (EO) dimensions on firm performance in the tourism sector. The goal is twofold: on the one hand, the paper aims to test whether EO dimensions are still significant determinants of performance after controlling for possible confounding factors; on the other hand, it aims to address the question of which EO dimension exerts the strongest effect on performance. Design/methodology/approach - A survey was carried out in the Sardinian accommodation sector in 2012 and 224 questionnaires were collected. The multidimensional EO constructs were adopted. Findings - The results show that innovativeness, proactiveness and autonomy were significantly associated with tourism firm performance, whereas risk-taking and competitiveness were not. Research limitations/implications - The results are limited to the Sardinian accommodation context. Self-reported data were used to measure firm performance. Further research works could replicate the analyses using objective firm performance not only in similar touristic destinations but also in other countries and incorporating other industries. Practical implications - The study suggests educational and managerial implications. Entrepreneurs in the tourism sector should be encouraged to adopt an innovative, autonomous and proactive approach in managing their firms. Originality/value - The study advances entrepreneurial knowledge in the tourism sector and in particular in the accommodation industry. The multidimensional EO approach has never been adopted among touristic firms. Furthermore, considering that EO research has been overlooked in the country of Italy, this study's contribution is also providing evidence from an area that has received minimal attention to date.
Keywords: 650; Entrepreneurial orientation; Multidimensional approach; Accommodation sector; Ordered logit regression; Tourism sector